Sustainability spillover effects and partnership between East Asia & Pacific versus North America: interactions of social, environment and economy - Nodehi, Mehrab; Arani, Abbas Assari; Taghvaee, Vahid Mohamad (Letters in spatial and resource sciences, 2022)
The three sustainability pillars of social, environment and economy were initially introduced by the United Nations in 2002, addressing major global sustainability issues including economic problems, income inequality, environmental pollution and social shortcomings. Comparing East Asia & Pacific with North America, there is a growing concern over economic, political and even social competition as a result of recent development and industrialization that is taking place in Asian countries. This might lead to an unhealthy conflict that favors regional independency as opposed to the current globalization and trade facilitation trend. As a result, this study aims to assess the effects of development in three main pillars of sustainability (social, environment and economy) in the East Asia and Pacific on that of North America and vice versa. To estimate this interactive or spillover effects of sustainable development (or sustainability elasticities), our research employs Econometric methodologies including Simultaneous Equations System, Vector AutoRegressive (VAR) and Granger Causality approaches during 1971–2016. The results show that most of the sustainability elasticities are positive between and inside the two regions, supporting the synergetic character of the sustainability spillover effects and confirming constructive role of globalization and openness in the sustainability progress. Based on the results, this research suggests policy-makers to follow cooperative and flow-based governance rather than the placed-based or regional independent thinking that supports integrated sustainable development benefiting not only the two parties but also the overall global sustainability.